2001
DOI: 10.1093/nar/29.17.3657
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of mammalian mitochondrial DNA replication: import of mitochondrial transcription factor A into isolated mitochondria stimulates 7S DNA synthesis

Abstract: The light strand promoter of mammalian mitochondrial DNA gives rise to a primary transcript, but also to the RNA primer necessary for initiation of replication and 7S DNA synthesis as well as 7S RNA. Here we have studied the turnover of 7S DNA in isolated rat liver mitochondria and whether import of mitochondrial transcription factor A (mtTFA), which is necessary for transcription initiation, increases its rate of synthesis. 7S DNA was present as two species, probably due to two different sites of RNA-DNA tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 26 publications
5
50
0
Order By: Relevance
“…Because CV values are very similar at the G3 and G4 stages for embryos produced by the two procedures, one hypothesis which might explain increased levels of donor cell heteroplasmy in the initial stages of NT-F embryo development would be that somatic mitochondria may be able to replicate during the initial phases of embryo development independent of embryonic control, because these mitochondria may have brought essential enzymes with them from the somatic cells (Gensler et al, 2001;Wiedemann et al, 2004). This replication could explain the greater quantity of mtDNA in the fourth stage (G4) of embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…Because CV values are very similar at the G3 and G4 stages for embryos produced by the two procedures, one hypothesis which might explain increased levels of donor cell heteroplasmy in the initial stages of NT-F embryo development would be that somatic mitochondria may be able to replicate during the initial phases of embryo development independent of embryonic control, because these mitochondria may have brought essential enzymes with them from the somatic cells (Gensler et al, 2001;Wiedemann et al, 2004). This replication could explain the greater quantity of mtDNA in the fourth stage (G4) of embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments clearly underlined the vital importance of this protein, however, they could not distinguish between the two possible TFAM roles in mtDNA maintenance, namely its involvement in replication initiation vs. mtDNA binding. We have shown that import of TFAM into isolated mitochondria stimulates the rate of transcription and initiates synthesis of DNA [27,28] and that overexpression in HeLa and HEK cells increases mitochondrial transcript levels, but is not sufficient to increase mtDNA copy number [29], emphasizing its role in transcription regulation in situ. The concentration of TFAM and mtDNA was measured in mitochondria from human placenta [30] and mouse kidney [31] and the authors found enough TFAM to completely cover all mtDNA molecules.…”
Section: Organization Transcription and Replication Of Mtdnamentioning
confidence: 98%
“…However, it is not known if a specific initiation event is required for DNA replication, perhaps guided by a given factor (Shadel & Clayton, 1997). mtTFA could be involved in this process since this protein seems to be required, particularly for L-strand transcription initiation, and the heterozygous knock-out mice for this factor show reduced mtDNA levels (Larsson et al 1998;Gensler et al 2001). A second point of possible regulation is the cleavage of nascent RNAs for primer formation.…”
Section: Regulation Of Mtdna Expressionmentioning
confidence: 99%